Peran United Nations Children’s Fund (UNICEF) Dalam Melindungi Hak-Hak Anak Korban Konflik Bersenjata Antara Palestina Dan Israel - Kanda Ramandana; Vina Maharani (Uniku Law Review, 2024)
In essence, every child has the right to life, security, comfort and growth, just like adults, but children are felt to be very vulnerable to various things. Persecution and victims in war are very inhumane acts against children, with war In addition, child abuse can cause children to feel insecure or rob them of their rights as humans and children, such as a sense of security, comfort and growth and development. By using the Normative Juridical Method, we can get a view regarding the role of protecting children in the international organization UNICEP as a problem solver, as a collective action mechanism, as a capacity builder, as an aid provider. Based on this, in the case of children who are victims of war, it cannot be tolerated. Law enforcement is clear in Article 77 of the Rome Statute which contains laws for perpetrators of crimes which include committing crimes by abusing children and even killing innocent children.